Türkiye in International Energy Trade: Implementation of Social Network Analysis - Yücel, Mustafa; Turan, Erol (Journal of the Human and Social Sciences Researchers, 2024)
Energy resources are fundamental inputs in almost every sector and play a crucial role in development and economic stability. This situation has increased the importance of keeping energy costs low, becoming a significant factor in attaining global superiority. In the contemporary era, where states represent the highest level of the organization, the strategic importance of these resources has been further exposed. The strategic value of energy resources, predominantly encompassing fossil fuels such as oil, natural gas, and coal, has precipitated intense global competition. The dynamics of energy resource trade have transcended mere profit-driven motives, transforming into a tool wielded by governments for various political objectives. This paradigm shifts underscores the vitality of energy supply security, prompting the formulation of energy trade networks guided by policies and national strategies. Within these networks, participating actors exhibit diverse traits shaped by distinct circumstances, assuming varied roles through pre-existing relationships. The purpose of the research is to examine the energy trade network of Türkiye, implementing the social network analysis method that integrates empirical data and mathematical approaches. The study aims to unveil pivotal aspects of the network, including its size within the global energy trade landscape, density, relational ties among actors, centrality, and brokerage degrees. The research aims to contribute valuable insights to understanding Türkiye's positioning in the global energy trade through these analyses. The results indicate that the volume of Türkiye's energy trade network accounts for around 1/3 of the global energy trade. While no single dominant actor exists in the network, specific entities demonstrate significant brokerage power. The analysis highlights the impact of global energy players, including Russia, the United States, and some European countries. Finally, the study involves recommendations for future research, anticipating a continued exploration of the complicated dynamics shaping energy trade networks on a global scale.
Keywords: Stratejik Yönetim; Sosyal Ağ Analizi; Sürdürülebilir Enerji Ticareti; Enerji Güvenliği; Uluslararası İşletme; Strategic Management; Social Network Analysis; Sustainable Energy Trade; Energy Security; International Business; Strateji, Yönetim ve Örgütsel Davranış (Diğer); Strategy, Management and Organisational Behaviour (Other); 9. Industry and infrastructure; 16. Peace & justice; 7. Clean energy